Ultrathin optically transparent electromagnetic shielding window with broadband microwave absorption and ultrahigh optical transmittance. Issue 11 (1st August 2022) - Li, Shuying; Liu, Liangliang; Jiang, Yuying; Tang, Chunzi; Gu, Changqing; Li, Zhuo
Abstract: In this work, we propose an optically transparent metamaterial absorber (OTMMA) based electromagnetic interference shielding window with broadband microwave absorption and ultrahigh optical transmittance. Such a window with relative thickness of λ 0 /21.4 at the lowest frequency consists of a three‐layer structure in which two indium‐tin‐oxide films with different patterns are etched on the upper and lower surfaces of a glass substrate. The specific design feature realizes more than 90% microwave absorption covering a wide frequency range of 7.84–12.35 GHz and makes the window insensitive to the incident angle and polarization state of the incident microwave. Importantly, the measured shielding effectiveness of the window is larger than 25 dB in the range of 8–12 GHz, while the average optical transmittance is higher than 93% in the visible region. In addition, the absorption mechanism is revealed through an equivalent circuit model and the electric field and surface current distributions on the structure. The proposed shielding window provides a significant route to realize broadband microwave absorption and high optical transparency, enabling potential applications in the window glass of stealth armament and medical precision apparatus.